Applied Catalysis B: Environment and Energy - Applied Catalysis B: Environment and Energy (Elsevier, 2026)
Applied Catalysis B: Environment and Energy warmly welcomes original, innovative, and high-impact contributions within the realm encompassing thermo-, electro-, and photocatalysis to advance clean energy and provide sustainable environmental solutions.
FI 2.99
Q1
Keywords: Chemistry; Catalysis; Medio ambiente; Energía; Acuerdos transformativos; Transformative agreements; Termocatálisis; Electrocatálisis; Fotocatálisis